Implementing Lectio Divina in Spiritual Revitalization of Protestant Pastors in Indonesia - Saragih, Jaharianson; Sipayung, Parulihan (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
The purpose of this study is to explore and implement the practice of Lectio Divina and analyze its theological and practical implications for the spiritual growth of Lutheran pastors in North Sumatra, Indonesia. We argue that Lectio Divina is effective for enhancing the spirituality of pastors. This research employs a participatory action research design with qualitative orientation and limited quantitative pre-post measurement. There are several things this study aims to accomplish, namely: to explore the early understanding of Lectio Divina, to delve deeper into and to unravel the history of its emergence and development, and the application of this practice in the ecumenical church in the 21st century. This article also explains the four practical steps of the Lectio Divina spiritual formation. The research found that the implementation of Lectio Divina among pastors had a significant impact on their spiritual growth and behavior. Finally, the author proposes the practice of Lectio Divina can be contextually applied in Indonesian Lutheran churches.